2021
DOI: 10.1177/00938548211042057
|View full text |Cite
|
Sign up to set email alerts
|

International Survey on the Use of Emerging Technologies Among Forensic and Correctional Mental Health Professionals

Abstract: Although the global diffusion of e-mental health has increased in recent years, research on the use of technologies in criminal justice settings is limited. To bridge this knowledge gap, we conducted an international online survey ( N = 555) of forensic and correctional mental health professionals from Germany, Switzerland, the United Kingdom, the United States, and 20 additional countries. Telecommunication technologies and mental health platforms had the highest numbers of users, the broadest scope, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…This special issue includes eight articles covering a myriad of topics of interest to an international readership and reflecting the current state of e-mental health research and practice in criminal justice settings. In the first article, Kirschstein and colleagues (2023) conducted an international online survey exploring the use of technology for providing clinical services among forensic and correctional mental health professionals. Results showed that mental health professionals are using a number of technologies in forensic and correctional practice with some frequency to accomplish a variety of clinical tasks.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…This special issue includes eight articles covering a myriad of topics of interest to an international readership and reflecting the current state of e-mental health research and practice in criminal justice settings. In the first article, Kirschstein and colleagues (2023) conducted an international online survey exploring the use of technology for providing clinical services among forensic and correctional mental health professionals. Results showed that mental health professionals are using a number of technologies in forensic and correctional practice with some frequency to accomplish a variety of clinical tasks.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Based on the definition of the World Health Assembly (2005), e-mental health refers to the use of information and communication technologies for mental health. The range of technologies falling under this term is broad and covers telecommunication (e.g., telephone calls, videoconferencing, and emails), social media (e.g., internet fora, social networks, and wikis), digital platforms (e.g., mobile apps, desktop applications, and websites), and advanced technologies (e.g., decision support systems, virtual reality, and wearable technology; Kirschstein et al, 2023). In forensic and correctional mental health, such technologies have been used to perform expert testimony in court, monitor behavior in high-risk situations, and assess deviant sexual interests (Batastini et al, 2020; Fromberger et al, 2018; Renaud et al, 2014).…”
mentioning
confidence: 99%
“…From January to March 2021, Kirschstein et al. (2021) distributed their survey to forensic and correctional mental health clinicians in 24 countries, including the United States. The 555 respondents were accessed via professional organizations and a non‐probability snowball sampling method.…”
Section: Introductionmentioning
confidence: 99%
“…Viglione and colleagues (2020) identified large increases in the use of telehealth for mental health and substance use treatment provisions in community corrections, which were not commonly used prepandemic (Viglione et al, 2020). The findings of Viglione and colleagues (2020) were supported by recent research that found nearly 63% of mental health professionals reported great increases in their use of videoconferencing to provide telehealth in criminal justice settings because of the pandemic (Kirschstein et al, 2021). While prior to the pandemic, approximately 20% of telehealth services involved justice-involved individuals (Lowes, 2001), these were primarily focused on individuals in prison or jail (Ax et al, 2007).…”
mentioning
confidence: 97%